Impulses of a Question in the Margin: A Review of the Contribution of Hispanic Medievalism to Royal Court Studies - Gamero Igea, Germán (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
Medievalists, and specifically Spanish medievalists, have been considered as an academic group not interested in the Court history until the 80’s or 90’s of the twenty century. In this paper I propose reconsider this statement by analyzing how courtier topics were present in medieval scholars at the beginning of the century. Thanks to their efforts medievalism could (and can, nowadays) propose some interesting questions about royal entourages and its evolution.
Keywords: Court Studies; Medievalism; royal courts; Hispanic Studies